This preview shows pages 1–3. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.View Full Document
Unformatted text preview: Sequences and Recursion Mariusz Bajger COMP2781/8781 School of Computer Science, Engineering and Mathematics April 4, 2011 1/ 35 Reading and Exercises Reading Epp, Chapter 5 Exercises Start with the blue ones in Sec. 5.1 to 5.8 Good learning strategy: BE ACTIVE! I Regularly revise lectures I Solve the suggested exercises I Be critical when reading textbook/lectures I Ask your colleagues, ask the lecturer, dont be shy! I It is OK to ask for help any time 2/ 35 Sequences Definition A sequence is a function whose domain is either all the integers between two given integers or all the integers greater than or equal to a given integer. A sequence can be finite a m , a m +1 , a m +2 ,..., a n n m terms or infinite a m , a m +1 , a m +2 ,... infinite number of terms EXAMPLE (explicitly defined sequence) Let s n = 2 n + 4 3 n , n Z , n 2. Then s n 1 = 2 n 1 + 4 3 n 1 . Find s n 2 ? 3/ 35 Summation notation Summation from k ( summation index ) equals m ( lower limit ) to n ( upper limit ) of a-sub- k : n k = m a k = a m + a m +1 + a m +2 + + a n For example, 5 i =0 ( 1) i i + 1 = 0 1 2 + 2 3 3 4 + 4 5 5 6 EXAMPLE (Telescoping sum) Use the formula 1 k ( k +1) = 1 k 1 k +1 to show that n k =1 1 k ( k + 1) = 1 1 n + 1 4/ 35 Product notation Product from k equals m to n of a-sub- k : n k = m a k = a m a m +1 a m +2 a n For example, 5 i =1 i i +1 = 1 2 2 3 3 4 4 5 5 6 = 1 6 Theorem (properties of sums and products) n k = m a n + n k = m b k = n k = m ( a k + b k ) c n k = m a k = n k = m c a k ( n k = m a k ) ( n k = m b k ) = n k = m ( a k b k ) 5/ 35 Change of variable in sums Similar to changing variable in integrals. For example, replace the index i by k in the sum n i =1 i 2 r n i where i = k + 1. Steps: I find the lower and upper limits of the new summation when i = 1 , k = 0 and when i = n , k = n 1 I find the general term of the new summation (replace i by the new index k ) i 2 r n i = ( k + 1) 2 r n k 1 I put it together n i =1 i 2 r n i = n 1 k =0 ( k + 1) 2 r n k 1 6/ 35 n Choose r notation ( n r ) Reminder: (factorial definition), for n Z + n ! = n ( n 1) 3 2 1 = n k =1 k and 0! = 1 Definition For n , r Z : 0 r n we define n choose r ( n r ) which represents the number of subsets of size r that can be selected from a set of n elements. Later, we will prove that ( n r ) = n ! r !( n r )! 7/ 35 Sequences in computer programming One-dimensional arrays a  , a  , a  ,..., a  are finite sequences....
View Full Document
- Spring '08